Adsorption and Desorption Behavior of Cr(VI) on Two Typical UV-Aged Microplastics in Aqueous Solution - Hu, Chun; Xiao, Yaodong; Jiang, Qingrong; Wang, Mengyao; Xue, Tingdan; Tao, Ruidong; Mei, Yunjun (Langmuir, 2024)
Microplastics (MPs) are novel pollutants that can adsorb heavy metals in water environments and migrate together as carriers and are prone to aging due to the light in water. However, few reports have been published on the synergistic behavior and effects of these different types of aged MPs on the adsorption and desorption of Cr(VI). Here, two MP typespolyamide (PA) and polylactic acid (PLA)were aged by UV irradiation, and the adsorption and desorption behaviors of MPs on Cr(VI) were studied. The results indicated that UV light can rapidly age MPs. After the MPs were exposed to UV light, their specific surface area, negative charge, and oxygenic groups increased, resulting in enhanced hydrophilicity. The aged MPs depicted a markedly enhanced adsorption capacity for Cr(VI) compared with the results of aged-PA > pristine-PA > aged-PLA > pristine-PLA. The process followed the Langmuir and pseudo-second-order models, confirming that chemical and monolayer adsorption are the primary processes involved in the adsorption of Cr(VI) by aged MPs. Cr(VI) was more easily desorbed in the simulated gastric fluid environment. The desorption rate of aged MPs was lower than that of pristine MPs because of their stronger binding forces to Cr(VI). The binding of Cr(VI) to MPs mainly depends on synergistic mechanisms such as electrostatic attraction, reduction reactions, and chelation of oxygenic groups. This study clarifies the reciprocity mechanism between aging MPs and Cr(VI) and provides further insights and guidance for controlling the joint pollution between MPs and heavy metal pollutants in the future.